Geriatric depression and the factors associated among the elderly residing at the state elder’s home, Jaffna district of Sri Lanka - Kasiyanantham, K.; Jayathilaka, D.D.; Sathees, S.; Kajavinthan, K. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka, 2023)
Introduction: Geriatric depression is a common mental and emotional disorder in elderly population. Recent economic and social changes in Sri Lanka resulted an increase number of elders spending their remaining years in elderly homes. Institutionalized elderly are more vulnerable for geriatric depression. Objective: To assess the level of geriatric depression and its associated factors among the elderly residing at the state elder’s home, Jaffna district of Sri Lanka. Methodology: This was an institutional based descriptive cross-sectional study among 144 elderlies. An interviewer-administered questionnaire was used to gather the data. IBM SPSS version 25 was used to analyze the data and chi squared test was performed to identify the significant association of geriatric depression with various factors. Results: The study shows the mean age of the participants was 72.08 years (SD±7.637) with the majority of males (54.9%). Three fourth of the participants were (76.4%) presented with Geriatric Depression. Level of Geriatric Depression was significantly associated with educational background (p=0.047), previous employment status (p=0.006), chronic disease (p=0.014), clinic follow-up (p=0.007), regularity of recreational activities (p=0.009), institutional environment arrangements (p=0.032), level of satisfaction with care providers (p=0.005), friends and social connection (p=0.017), and level of support of elders' home in coping to stress (p = 0.002). Conclusion: The prevalence of depression among elderly people in the State elderly home at the Jaffna district was high. The Level of geriatric Depression is associated with various modifiable factors. The interventions to reduce the Depression among institutionalized elderly is necessary. It is recommended that the interventions should focus on the factors identified in the current study.
Keywords: Geriatric depression,; Elderly; Jaffna